Financial education and the debt behavior of the young - Meta Brown; Wilbert van der Klaauw; Jaya Wen; Basit Zafar (Federal Reserve Bank of New York, 2013)
More than three-quarters of U.S. households bear consumer debt, yet we have little understanding of the relationship between financial education and the debt behavior of U.S. consumers. In this paper, we study the effects of exposure to financial training on debt outcomes in early adulthood. Identification comes from variation in financial literacy, economics, and mathematics course offerings and graduation requirements mandated over the 1990s and 2000s by state-level high-school curricula. The FRBNY Consumer Credit Panel provides debt outcomes based on quarterly Equifax credit reports from 1999 to 2012. Our analysis, based on a flexible event-study approach, reveals significant effects of financial education on debt-related outcomes of youth. On the extensive margin, financial literacy education has a sizable impact on the propensity of youth having a credit report. Conditional on having a credit report, on the intensive margin, math and financial literacy education exposure reduces the incidence of adverse outcomes - such as accounts in collections and delinquent accounts - and reduces both the likelihood of youth carrying debt and their average debt balances. The net effect of both math and financial literacy education is an increase in youths' average creditworthiness, as measured by the Equifax risk score. On the other hand, economic education increases the likelihood of individuals carrying balances, leads to significant increases in debt balances - in particular, debt used to support consumption - and, at the same time, increases the likelihood of adverse credit outcomes, leading to a decline in youths' average risk scores. The effects of these financial education policies accumulate over the course of early adulthood. Our results suggest that financial education programs, increasingly promoted by policymakers, are likely to have significant impacts on the financial decision-making of youth, but the effects depend on the content of these programs.
Keywords: A20; D12; D14; 330; financial literacy; debt